Post Neo-Liberalism and the Humanities: What the Repressive State Apparatus Means for Universities - Hyslop-Margison, Emery J.; Leonard, Hugh A. (Canadian Journal of Higher Education, 2012)
In this article we explore how neo-liberal and post neo-liberal policies threaten the humanities in post-secondary education as a potential site of democratic dialogue and social transformation. We distinguish between neo-liberalism and post neo-liberalism on the basis of the latter’s increased police suppression of democratic dissent. We are especially concerned with the impact of the repressive state apparatus on the critical public spaces traditionally provided by a humanities education. In response to this threat, we propose encouraging university faculty to assume a far more active political role in educating the general public on the relationship between the humanities and democratic societies.